Seroprevalence of hepatitis viruses and risk factors in blood donors of Veracruz, Mexico - Nayali Lopez-Balderas; Elide Bravo; Mireya Camara; Pablo Hernandez-Romano (Journal of Infection in Developing Countries)
Introduction: Hepatitis B and C are among the most important transfusion-transmitted infections and sources of liver diseases worldwide. In Veracruz, Mexico, liver diseases are important causes of mortality, and the prevalence reports of these viruses are scarce. This study sought to determine the prevalence of these infections in blood donors, in order to increase the safety of blood products in this region. Methodology: A retrospective study was performed on blood donors who attended the Veracruz State Blood Transfusion Center from 2006 to 2010. All samples were screened for transfusion-transmitted infections. The prevalence rates of hepatitis B virus (HBV) and hepatitis C virus (HCV) were determined, and demographic data obtained from clinical records were used to evaluate risk factors. Results: A total of 56,377 donors were serologically screened; of them, 403 were seropositive for HCV (357 men and 46 women), and 61 were positive for HBsAg (52 men and 9 women). The overall prevalence rates were 0.72% (0.63%–0.76%) for HCV and 0.11% (0.08%–0.14%) for HBsAg. The risk factors for HBsAg positivity were being a cattleman and living in the Huasteca Baja region, whereas those for HCV were being a fisherman, living in the Papaloapan region, and having an elementary-level or lower education. Conclusions: This is the first study to show that being a fisherman is a risk factor for HCV. The implementation of nucleic acid test technology will help to identify the real risks for transfusion-transmitted hepatitis C in Veracruz.